Foreign Currency Loans and Credit Risk: Evidence from U.S. Banks - Friederike Niepmann; Tim Schmidt-Eisenlohr (Center for Economic Studies and ifo Institute (CESifo), 2017)
When firms borrow in foreign currency but collect revenues in local currency, exchange rate changes can affect their ability to repay their debt. Using loan-level data from U.S. banks' regulatory filings, this paper studies the effect of exchange rate changes on firms' loan payments. A 10 percent depreciation of the local currency makes a firm with foreign currency debt 69 basis points more likely to become past due on its loans than a firm with local currency debt. This result implies that firms do not perfectly hedge against exchange rate risk and that this risk translates into credit risk for banks. The findings lend support to both the balance sheet channel and the financial channel of exchange rates.
Keywords: F31; G15; G21; 330; cross-border banking; exchange rates; credit risk; corporate loans